City and empire in the age of the successors : urbanization and social response in the making of the Hellenistic kingdoms - Boehm, Ryan (University of California Press, 2018)
In the chaotic decades after the death of Alexander the Great, the world of the Greek city-state became deeply embroiled in the political struggles and unremitting violence of his successors' contest for supremacy. As these presumptive rulers turned to the practical reality of administering the territories under their control, they increasingly developed new cities by merging smaller settlements into large urban agglomerations. This practice of synoikism gave rise to many of the most important cities of the age, initiated major shifts in patterns of settlement, and consolidated numerous previously independent polities. The result was the transformation of the fragmented world of the small Greek polis into an urbanized network of cities. This text provides a new approach to this encounter between imperial powers and cities in northern Greece and Asia Minor